Evaluación de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en el cantón Saquisilí. - Barrera Muñoz, José Miguel (2023)
In Saquisilì Canton, evaluation of economically important traits in milk production was carried out, which were determined based on genetic improvement objectives. The methodology was performed by taking data and records, to establish by economic analysis the selection objectives based on profitability: lactation days, age at first calving, days open; and milk production traits variability: weight gain of bovines, milk weight in kg, milk density, mastitis test by California Mastitis Test (CMT), in such a way that all of them are correlated and the ideal animals are selected. The results show a total of 28 cows within the project with 72% cows in production, 14% cows in gestation and 14% heifer; with a rope use system, feeding based on agricultural waste and lack of records; the genetic selection objectives variability and the traits of economic importance in milk production indicate: lactation Days (141 days) with projection towards 305 days, age at first calving (37.55 months) which exceeds the estimated 24 months, days open (151 days); these objectives are reflected in a total economic loss of $14,744.00 dollars/year. In addition, average WG (weight gain) for November, December and January (545.55 gr/day), optimal milk production according to the environmental conditions of the canton (8.68 kg) with the crossbred cows having the best milk yield (10.36 kg/day), milk density (26.36) and 71% with negative results for the subclinical mastitis presence, showing an adequate control of milking practices. Evaluation ranges are established for each criteria for breeding stock selection, thus giving 2 cows that fit the established traits and will be considered as mothers of breeding stock for the dissemination of genetic material; it is clear that everything is associated with the cattle production systems profitability.